UJI SENSITIVITAS BEBERAPA ANTIBIOTIK TERHADAP BAKTERI GRAM-NEGATIF YANG DIISOLASI DARI ULAR SANCA BATIK (Python reticulatus) - , MAULIDA P A P, Dr. drh. Agustina Dwi Wijayanti, M.P. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Reptile can be a reservoir of microorganism disease in humans and other animals. Mouth rot disease caused by Gram-negative bacteria is one of the diseases that often (high rate incident) infect the snake. Therapy of Gram-negative bacteria infection in the snake is usually done with enrofloxacin, doxycycline and penicillin, but the improper use of antibiotics doses and frequency to the snake can lead to resistance. Therefore, it is necessary to do research with aim to isolate Gram-negative bacteria from Python reticulatus which have symptom of mouth rot and look for the sensitivity to some antibiotics. This study used 10 Python reticulatus. The culture took from each cloacal swabs, oral swabs, blood swabs with heparin and blood swabs with ethylene diamine tetraacetic acid (EDTA) respectively. Isolation to gram-negative bacteria were used Brilliant Green Agar (BGA) media. Gram-negative bacteria which grown tested the sensitivity to flumequin, enrofloxacin, amoxicilin, amikacin, doxycycline, and gentamicin by disk diffusion method. From 40 swabs can be isolated 6 (15%) Gram-negative bacteria that can fermentating the lactose (fermented lactose / FL) and 12 (30%) bacteria that canât fermentating the lactose (non-fermented lactose / NFL). Sensitivity test results showed that Gram-negative FL bacteria intermediate to enrofloxacin, amikacin dan gentamicin, but sensitive to amoxicilin, whereas Gram-negative NFL bacteria sensitive to enrofloxacin, amikacin, dan gentamicin, but resistant to amoxicilin.